Percutaneous cerclage wiring for type 34-C patella fracture in geriatric patients. Issue 6 (June 2020) - Zhai, Qilin; Yang, Jun; Zhuang, Jian; Gao, Rufeng; Chen, Mingji
Highlights: Minimal invasive surgery. No postoperative infection. Easy removal of internal fixation. Abstract: Purpose: This study was to retrospectively evaluate clinical outcomes of geriatric patients with patella fracture treated by percutaneous cerclage wiring and to introduce the surgical technique. Methods: From January 2009 to December 2015, fifty-seven consecutive geriatric patients of type 34-C patellar fracture underwent closed reduction and percutaneous cerclage wiring fixation in our hospital. Visual Analog Scale (VAS) score, Levack score system, WOMAC test form of pain, stiffness and function, and knee joint range of motion (ROM) were applied for functional evaluation. Results: Fifty-three patients were followed up for a mean period of 36 months (12 to 82 months). All fractures were unioned, no wound infection, second displacement of fracture fragment or wire migration was found. Wire breakage happened in one case at six months post-operation. Thirteen patients had hardware removed, nine cases for implant irritation at the knot and four cases for no specific reason. No patient developed postoperative knee stiffness, and range of motion was 128.6° (110–140). The average VAS score of emotional knee function was 87.5 (65–99) preinjury and 78.1 (53–95) at the last follow-up. 86.8% (46/53) patients considered that they regained more than 80% of their knee function. The average Levack score was 10.0 (6–12), which included thirty-five evaluations of "excellent" and eighteen of "good". The average WOMAC score was 21.3 (13–37). Conclusions: Percutaneous cerclage wiring fixation is a viable option for type 34-C patella fracture in geriatric patients.